Reversible inhibition of reproduction during regeneration of cerebral ganglia and celomocytes in the earthworm Dendrobaena veneta - J Okrzesik; N Kachamakova-Trojanowska; A Jozkowicz; A J Morgan; B Plytycz (Invertebrate Survival Journal, 2013)
Earthworms may be subjected to mechanical/chemical stimuli and/or sub-lethal predator attacks leading to the extrusion of celomocytes and/or loss of body parts; thus, regeneration of cells, tissues and organs has adaptive value. The aim of present study on the lumbricid earthworm Dendrobaena veneta was to determine the interactive effects of celomocytes and the brain on the regeneration of either system after experimental depletion or extirpation, and to assess the effects of such treatments on reproductive performance. Decerebration was achieved either by amputating the first six anterior segments, or by surgery; celomocyte depletion was achieved by a standard electro-stimulation procedure. Celomocytes (amebocyte and eleocytes, respectively) were counted by hemocytometry, and riboflavin content in celomocyte lysates measured by spectrofluorimetry. The main findings were: (i) D. veneta regenerated anatomically intact brain, including neurosecretory cells, within 10 - 18 weeks after its removal plus celomocyte depletion (i.e. dual treatment); (ii) amoebocyte counts recovered to control levels by 10 weeks after extrusion treatment alone, but were still lower (60 %) than in controls at 18 weeks after dual treatment; eleocyte recovery after electro-stimulation alone was slow, reaching control levels only after 18 weeks, and was further retarded (31 % of controls at 18 weeks) by brain extirpation; (iii) riboflavin content was lower than controls only in the dual-treatment worms at 5 weeks; riboflavin content relative to eleocyte numbers was initially higher than controls in both treatment groups; this index was restored to control levels by 18 weeks in the electro-stimulation only treatment whilst recovery was somewhat retarded in the brain-extirpated group; (iv) celomocyte depletion treatment alone slightly impaired reproductive output, whilst brain removal had pronounced and protracted inhibitory effects. The observations engender the hypothesis that brain-derived neurosecretions and immune-competent celomocytes act in tandem to modulate neural regeneration and reproduction.